تقييم التأثيرات الجانبية لبعض المركبات غير المتخصصة من مجاميع كيميائية مختلفة على الصفات الحيوية للأكاروس الأحمر ذي البقعتين مخبرياً Tetranychus urticae Koch (Acari :Tetranychidae) - صقر ابراهيم; غالية سهير (Latakia University Journal -Biological Sciences Series, 2018)
اختبرت التأثيرات الجانبية الإيجابية لعشرة مركبات مختلفة ضمن ظروف المخبر على بعض الصفات الحيوية للأكاروس T.urticae باستخدام طريقة الأقراص الورقية, وهي المبيدات: أكاروسية حشرية (فيرتميك, تلستار, ماجستر), حشرية أكاروسية ( روكسيون, بوسّه), فطرية أكاروسية ( توبسين م, ثيوفيت), حشرية ( أريفو), فطرية ( بايكور), مانع انسلاخ (ديميلين), واستعمل النسورون كمبيد قياسي. أظهرت النتائج نمو الأجنة في البيوض المعاملة بجميع المركبات لكن دون فقس للبيض لدى معاملات المركبين تلستار وماجستر وكذلك المبيد القياسي نسورون. خرج عدد قليل من اليرقات لدى معاملات المركبات فيرتميك، روكسيون، توبسين- م وبّوسه وبفروق معنوية عن الشاهد. حققت مركبات الفيرتميك , تلستار, روكسيون وتوبسين م نتائج جيدة على اليرقات المعاملة بها، ولم يسجل وصول الأفراد الحية الى الطور البالغ وبالتالي غياب وضع البيض في معاملاتها, وقد تأخر بلوغ الأفراد بمعدل 1- 2 يوم وموعد وضع البيض لمدة يوم واحد مقارنة مع الشاهد لدى معاملات الفيرتميك, توبسين م, ثيوفيت, ديميلين والروكسيون. كانت التأثيرات الجانبية للمركبات غير المتخصصة (فيرتميك، تلستار، ماجستر، روكسيون وتوبسين-م) مرتفعة على الاناث البالغة والتي تراوحت عند نهاية التجربة ما بين 100 - 80.5%. حدث وضع للبيض لدى كافة المعاملات باستثناء النسورون، ودون خروج لليرقات مع التلستار, ماجستر, ديميلين, أريفو ونسورون, وبتأخير 1- 2 يوم لدى الروكسيون, توبسين م, بايكور, ثيوفيت وفيرتميك مقارنة بالشاهد. تراجعت خصوبة الاناث كثيرا 97.34 – 34.67)%) وبفروق معنوية بعد معاملتها بالمركبات التي ذكرت مع حدوث تأخير في بدء فقس البيض وزمن بلوغ الأفراد المتبقية حية مقارنة مع الشاهد. The positive effects of ten compounds were tested on some biological characteristics of T.urticae by Leaf discs method in laboratory. the pesticides: Acari- insectcides( Vertimec, Talastar, Magister), Insect- Acaricides (Roxion, Posse), Fungi- Acaricides ( Topsin-M, Thiovit), Insecticide (Arrivo), Fungicide (Baycor), Anti-ecdysis (Dimilin), and Nissorun was used as standard pesticide. Results showed that embryonic development has accrued in eggs which treatment with all tested compounds, but without eggs hatching when the eggs were treated with Talstar and Magister and also with the standard pesticide Nissorun. Some hatching eggs were recorded when it treated with compounds Vertimec, Roxion, Topsin-M, Posse and with significant differences from the control. Vertimec, Talastar, Roxion and Topsin-M achieved good results on the larval treated, and there weren’t any recording to the possibility of larve to reach the adult stage so no placed eggs on the tested compounds , but reaching adult was also delayed 1-2 days and the placed eggs were also delayed 1day compared with the control in Vertimec, Topsin-M, Thiovit, Dimilin and Roxion. The side effects of non-specialized compounds (Vertimec, Talstar, Magister, Roxion and Topsin-M) were high on the adult females that reach at the end of the test between (80.5-100%). eggs placing were accrued with all testes except Nissorun, and without the hatching of eggs into larve in Talastar, Magister, Dimilin, Arrivo, and Nissorun , and with 1-2 days delaying in Roxion , Topsin-M , Baycor , Thiovit and Vertimec comparing with the control. Fecundity of female adult decreased a lot (34.67- 97.34%) after they were treated by the mentioned compounds with significant differences with delay in hatching and the time of reaching adults stage comparing with control.